Pribumi di Mata Kolonial dalam Kumpulan Cerpen Teh dan Pengkhianat Karya Iksaka Banu - Mega Widyawati; Eggy Fajar Andalas (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2021)
This research aims to discuss social and cultural aspects that are closely related to Indonesian history regarding events of colonialism in the collection of short stories entitled Teh dan Pengkhianat by applying new historicism. This is a descriptive qualitative research. The theory used to analyze the relevance of literary works as social documents is from new historicism, Stephen Greenblatt (1980). Besides, the theory used to investigate colonialist perspectives on indigenous peoples is form orientalism, Edward Said (1935). The results of this research are as follows. First, historical representations are marked by fear, restraint, compulsion, and counterforce of indigenous people in the colonial period before and after 1945. Second, social representation is marked by humanity, preparation, and persistence in dealing with the variola virus that occurred in 1644. Third, cultural representations are marked by the hard work of indigenous people for equal rights in clothing style until transportation. Data that demonstrates hard work is the existence (space, process, and object), identity (matching), and unity/multiplicity (merging) of indigenous peoples and colonialists.